Pengaruh Intellectual Capital dan Komposisi Dewan Komisaris Independen terhadap Nilai Perusahaan - Rini, Rini; Muzhaffar, Achmad Daffi (Akuntabilitas, 2024)
This study aims to examine the influence of intellectual capital and the composition of independent commissioners on the firm value. Intellectual capital is measured through the components of human capital, structural capital, and capital employed, while the composition of independent commissioners is measured based on the proportion of independent board members to the total number of board members. Firm value is measured using the Tobin's Q ratio. This study uses secondary data obtained from the annual reports of companies for the period 2019-2022. The data analysis method used is multiple linear regression. The findings of the study indicate a significant relationship between intellectual capital, board independence, and firm value. Human capital and capital employed exhibited a positive association with firm value, whereas structural capital and the proportion of independent directors on the board displayed a significant negative association